The Relation Between Student Mood and Handicrafts in the Constructivist Classroom - Županić Benić, Marijana (Revija za elementarno izobraževanje, 2018)
The purpose of this paper is to emphasize the importance of handicrafts from the perspective of various pedagogical perspectives. Although the findings of numerous researchers support the positive effects ofhandicrafts, those teaching methods are rarely used in school either. The empirical section of this paper aimed to explore the relation between student mood after performing a handicraft assignment and attitudes towards the assignment. A total of 16 students between the ages of 11 and 12 were sampled from the same classroom in order to conduct this preliminary study. All the students had previous experience with sewing, which was taught to them by their teacher, with whom they have been working on various handicraft activities since the first grade of elementary school. An anonymous survey was created and administered to the participants. The results of this study suggest that handiwork in the classroom has potential implications for improving the students’ mood and creating a positive learning environment.DOI: 10.18690/rei.11.2.109-118.2018COBISS-ID:
Keywords: constructivism; handicrafts; mood; sewing